Heterogeneous Capillary Interactions of Interface-Trapped Ellipsoid Particles Using the Trap-Release Method - Lim, Jin Hyun (Langmuir : the ACS journal of surfaces and colloids, 2018)
Heterogeneous capillary interactions between ellipsoid particles at the oil-water interface were measured via optical laser tweezers. Two trapped particles were aligned in either tip-to-tip (tt) or side-to-side (ss) configurations via the double-trap method and were released from the optical traps, leading to particle-particle attractions due to the capillary forces caused by quadrupolar interface deformation. On the basis of image analysis and calculations of the Stokes drag force, the capillary interactions between two ellipsoid particles with the same aspect ratio (E) were found to vary with the particle pairs that were measured, indicating that the interactions were nondeterministic or heterogeneous. Heterogeneous capillary interactions could be attributed to undulation of the interface meniscus due to chemical and/or geometric particle heterogeneity. The power law exponent for the capillary interaction Ucap ≈ r-β was found to be β ≈ 4 and was independent of the aspect ratio and particle configuration in long-range separations. Additionally, with regard to the tt configuration, the magnitude of the capillary force proportionally increased with the E value (E > 1) when two ellipsoid particles approached each other in the tt configuration